传承客家文化与精神的茶阳（大埔）会馆 = Char Yong association’s proliferation of the Hakka culture - 罗小菊 Loh, Sheau Jyu (2015)
传统文化的流失已经不是一个新的课题。早在上世纪90年代，许多客属会馆已经发现了这个问题，同时也发觉会馆缺乏年轻人的参与。自从讲华语运动在1979年开始，华人开始普遍使用官方所指的华语 （北方方言），通晓方言的华人在过去的35间锐减。语言是文化的载体，在方言快速消逝的环境中，这导致地缘性质的客属会馆面临了前所未有的挑战。为了吸引新一代不善方言的邑人，会馆纷纷建立了青年团，希望通过一系列的活动来促进邑人对于祖籍文化的认识。这项研究试着探讨客属会馆如何在日新月异的新加坡社会求存，主要讨论会馆是使用什么途径来弘扬传统的客家文化。通过分析会馆所办的活动以及所提供的设施来谈文化的传承。The gradual loss of traditional Chinese culture has been a topic talked about since the 1990s. Many clan associations had also identify it as an issue to be regarded seriously. Furthermore, the other issue was the lack of youth participation in these associations. Language plays an important role in the proliferation of traditional culture. However, since the start of the Speak Mandarin Campaign in 1979, the number of users of the various Chinese dialects had decreased drastically. This proves to be a troublesome challenge posed to the various dialect-group based associations. In order to appeal to the younger generation which is highly unlikely to be well-versed in their dialects, these associations started setting up youth organizations.By taking Char Yong Association as an example, this project aims to discuss how these associations proliferate the rapidly diminishing dialect-centric culture in Singapore.